THE DIFFICULTIES OF SEVENTH GRADE STUDENTS IN WRITING DESCRIPTIVE TEXT AT SMP NEGERI 2 PEMATANGSIANTAR - Joel Jefanya Manasye Marbun; Herman Herman; Anita Sitanggang (Jurnal Ilmiah Pendidikan dan Keislaman, 2025)
This study investigates the difficulties faced by seventh-grade students in writing descriptive texts at SMP Negeri 2 Pematangsiantar. Writing, as a productive language skill, requires mastery of various components including content development, organization, vocabulary, language use, and mechanics. However, many students still struggle to express ideas effectively in written English. Employing a descriptive qualitative research design, this study focused on analyzing students’ writing performance using Jacobs et al.’s (1981) analytical scoring rubric. Data were collected through a descriptive writing test given to 90 students from three different academic ability levels. Each writing sample was assessed based on five writing components. The findings revealed that the most frequent difficulties occurred in mechanics, with 511 total cases, followed by language use with 238 difficulties. Errors in vocabulary (53), organization (41), and content (1) were considerably fewer, indicating that while students generally understood the descriptive writing format, their ability to apply proper grammar and writing conventions remained limited. The results suggest that the students’ struggles were not primarily due to a lack of ideas, but rather insufficient control over the technical aspects of writing. This study highlights the importance of targeted instructional strategies in grammar and mechanics to support students’ writing development. Teachers are encouraged to incorporate explicit writing practice and feedback into the classroom to improve students’ overall proficiency in descriptive text writing.